2021
DOI: 10.1136/bmjopen-2020-044899
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 symptom surveillance in immunocompromised children and young people in the UK: a prospective observational cohort study

Abstract: ObjectivesTo describe the frequency of symptoms compatible with SARS-CoV-2 infection in immunocompromised children and young people in the UK during the SARS-CoV-2 pandemic. To describe patient/parent anxiety regarding SARS-CoV-2 infection in this cohort.DesignA prospective observational cohort study.Setting46 centres across the UK between 16 March and 4 July 2020. A weekly online questionnaire based on the International Severe Acute Respiratory and emerging Infections Consortium-WHO Case Report Form was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Symptom under-reporting is possible, particularly in participants with a baseline of symptoms from chronic disease, although less likely due to levels of anxiety in this cohort. 18 Hazard of infection is likely over-estimated due to self-selection bias with participants presumably responding to surveys more frequently in weeks they reported a positive PCR swab. The shielding precautions taken will have varied both between individuals and through the course of the pandemic, so the individual hazard of SARS-CoV-2 infection will vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom under-reporting is possible, particularly in participants with a baseline of symptoms from chronic disease, although less likely due to levels of anxiety in this cohort. 18 Hazard of infection is likely over-estimated due to self-selection bias with participants presumably responding to surveys more frequently in weeks they reported a positive PCR swab. The shielding precautions taken will have varied both between individuals and through the course of the pandemic, so the individual hazard of SARS-CoV-2 infection will vary.…”
Section: Discussionmentioning
confidence: 99%
“…Against the advice of many specialist clinicians and NICE, 16 many individuals were advised to adopt specific precautionary “shielding” measures, were subject to school closures, and have had reduced access to healthcare, causing significant burden on both them and their families. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the observation reported in a nationwide prospective survey conducted by Shaunak et al among immunocompromised children and young adults during the first wave of SARS-CoV-2 in the United Kingdom. 10 Out of 1490 immunocompromised children across 46 centres, 110 children had symptoms consistent with SARS-CoV-2 infection but none tested positive. 10 Reports on the impact of the use of rituximab in cDNS during the COVID-19 pandemic are scarce and the risk of developing SARS-CoV-2 infection post rituximab is unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Out of 1490 immunocompromised children across 46 centres, 110 children had symptoms consistent with SARS-CoV-2 infection but none tested positive. 10 Reports on the impact of the use of rituximab in cDNS during the COVID-19 pandemic are scarce and the risk of developing SARS-CoV-2 infection post rituximab is unclear. In a previous international survey of COVID-19 infection among 113 children with kidney disease receiving various immunosuppressants, only 11 (10%) received rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, identification of pediatric cases for whom mAbs are authorized can be difficult and require very complicated and expensive monitoring. A study planned to show the frequency of symptoms compatible with SARS-CoV-2 infection in pediatric patients with immunodeficiency has shown that despite 67.4% of study patients reporting one or more symptoms suggestive of suspected SARS-CoV-2 infection, of the 110 who were tested for virus none was positive for SARS-CoV-2 [ 25 ]. These results suggested an absence of symptom specificity in these patients, showing that symptoms of SARS-CoV-2 infection overlapped with those of chronic disease exacerbations.…”
Section: Do the Benefits Of Monoclonal Antibody (Mabs) Treatment For Covid-19 In Children And Adolescents Really Outweigh The Risks?mentioning
confidence: 99%